The Power Semantics in Self and Other Repertory Grid Representations: A Comparison between Obese and Normal-Weight Adult Women - Faccio, Elena; Belloni, Eleonora; Castelnuovo, Gianluca (Frontiers in Psychology, 2012)
According to systemic-constructivist theory, all psycho-pathological organizations are linked to specific meanings which are developed by the individual within problematic situations in the context of learning, particularly within the family. The aim of this empirical study is to support the theory that eating disorders are linked to the “power semantics”, concept developed by Ugazio. The hypothesis that the bipolar construct “winner/loser” and the associated meanings are predominant for obese people, has been verified by interviewing 44 women (22 obese/overweight; 22 controls) using the Repertory Grid Test developed by Kelly. The participants’ elicited constructs were classified according to their semantic content and the data compared using statistical techniques. The power semantics were more prevalent and important in the Obese Group than in the Control Group. These results are critically discussed, highlighting possible clinical developments.